Kesulitan Mahasiswa Dalam Mengkoneksikan Sigma, Area, dan Definisi Integral Tentu Secara Geometri - Tasman, Fridgo; Ahmad, Defri; Suherman, Suherman (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
Integral is one of major topics in Calculus course. Many university students fail in calculus course because their understanding on the concept of Integral especially in understanding definition of integral is low. This situation encourages us to design a calculus lesson to build students understanding on Integral especially integral definition by using Realistic Mathematics Education as an approach. For that, we try to design a series of instructional activities starting from introducing sigma to definition of Integral in order to know students difficulties in understanding this topic. Some first-year university students in Universitas Negeri Padang are chosen to test our Hypothetical Learning Trajectory (HLT) in our preliminary research. The result is students had difficulties in connecting the sigma, area and definition of integral. This happens because the students did not see that the activities that have been designed as a whole that cannot be separated. Therefore, it is recommended to design a series of instructional activities which is focus on connecting sigma, area and definition of integral.